The Implications of Social Solidarity in Islam (Journal of the College of Education for Women, 2019)
That interdependence in Islam is cooperation, love and fraternity and give and takeand let him look rich to the poor, every Muslim is himself liable hungry and poor no matterhow many races and colors. That interdependence is cruel, spending for God and is thegreatest supporter of charities that deal with housing, food and medicine for the unemployedand needy, and social solidarity the consolidation of the values of brotherhood and love,where is the greatest support of corrupt and concerted community and causes prosperity insocieties and has a significant impact on the unity of Muslims and their club and theircollection. The Islamic regime tops major systems in entrusting the achievement claimed thelives of needy groups to society and not churning out is that the State only to makeresponsibility for the continuation of daily life and the permanence of the conduct of its ownranks on solidarity. search includes several areas of concern for the elderly, the disabled andorphans and caring neighbor and guest rights. This is evident through all that in areas thatdealt with research, we find that social cohesion is an important and vital topic and needs tobe further studied and utilized in the process of the application on the ground of any societysectors and groups and classes and just so we can do our part social and religious in oursociety, especially at the present stage.